Tinjauan Literatur Analisis Insidensi Faktor Resiko Kejadian Malaria pada Balita di Wilayah Endemik - Hermayani; Novianty Mansyur, Tri (STIKes Hamzar, 2024)
Malaria is the most common malarial disease, causing high morbidity and mortality rates, especially in the countries where the disease is most common. Because the Balinese immune system is not fully developed, they are particularly vulnerable to malaria. This study reviews the literature on malaria infections and risk factors for malaria in malaria-affected areas within the region where the disease is most prevalent. This study analyses literature from many sources of information, such as journal articles, reports from health organizations, and other research documents that have been published in the last few years. The research findings identify various factors that influence the onset of malaria in under five years old, including as Numerous factors can contribute to malaria in a baby, including environmental factors, educational attainment of parents and guardians, use of insecticidal mosquito net, use of mosquito repellent, age factor, and economic position. The study's findings indicate that malaria inside malaria-affected areas remains low despite various preventive measures taken. The primary risk factor that was identified included poverty, insufficient health facilities, low use of insecticidal mosquito net, as well as environmental conditions that hindered the growth of Anopheles. In addition, changes in climate also negatively impact the distribution and growth of mosquito vectors, increasing the risk of malaria. The main findings of this study suggest that more comprehensive and long-term research is needed to combat malaria in bats. This payment must be used to support increasing access to health services, educating the public about the importance of malaria prevention, and implementing community-based interventions. The information obtained from this literature review is hoped to serve as a foundation for more effective planning and execution of policies to reduce malaria rates in endemic areas.